Analisis Kelebihan dan Kekurangan Media Belajar AI dalam Proses Pembelajaran PAI di Perguruan Tinggi - Nurlaili; Qolbi Khoiri; Eva Susanti; Muhammad Agus Ainur Rasyid (EduInovasi: Journal of Basic Educational Studies, 2024)
AI is used by humans to help simplify and complete tasks in everyday life. AI is also used in the world of education. Important research is carried out because the development of artificial intelligence (Artificial Intelligence) has changed many aspects of human life, especially the world of education. In the digital era, Artificial Intelligence plays an important role in helping lecturers and students face learning challenges and achieve academic success. The research results show that AI media has several advantages in the PAI learning process in higher education, namely: 1) Data Management Efficiency, 2) Personalization of Learning, 3) Effective Feedback, 4) Increased Teaching Effectiveness. The disadvantages are: 1) Lecturers and students are afraid that their work will be completely replaced by AI, 2) Security and privacy, 3) Plagiarism, 4) Students are lazier than before because the features offered make it very easy for students to complete their college work, 5) Artificial Intelligence (AI) does not have Common Sense, 6) AI is able to learn and work on its own like humans, but AI cannot understand the purpose of the information it was made, 7) Student literacy will decrease because they don't have to bother reading journals or books, and 8) Using AI for a long time can have the potential to become addictive.